GPS-free indoor location tracking in mobile ad hoc network (MANET) using RSSI - Ali, Adel; Abdol Latif, Liza; Fisal, Norsheila (IEEE, 2004)
More devices in the future will be wireless connecting to the Internet and also these devices can move within the coverage area of the mobile network. Mobile ad hoc network consists of devices or nodes that are able to communicate among themselves. These nodes also serve as routers and can dynamically move around arbitrarily at any speed in any direction resulting in an ever-changing topology of MANET. Due to mobility of nodes, the most challenging issue is to design a routing protocol that guarantees delivery of packets. In order to improve the network routing performance a limited casting technique will be adopted which requires the ability to establish position information. Once a node's location is determined, the distance between them can be derived and the number of hops to the destination can be computed. In this paper, a GPS-free indoor position tracking system has been developed that provides knowledge of geometric location of nodes in MANET.